Implementasi Teori Hukum dalam Reformasi Hukum Agraria di Indonesia - Abdullah Mansur; Rangga Andika; Prita Tusia Megana; Ahmad Fanny Grafiky; Sufiarina Sufiarina (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Agrarian law reform in Indonesia is a strategic effort to achieve social justice, reduce land ownership disparities, and optimize the sustainable use of agrarian resources. This article examines the implementation of legal theory as a conceptual foundation in agrarian law reform, integrating normative,sociological,and critical approaches. The study identifies various challenges, including overlapping regulations, conflicts of interest, weak law enforcement, and limited community participation in legislative processes. Through qualitative analysis, this research explores how critical legal theory can drive policies that are more equitable and responsive to social dynamics. The findings reveal that the success of agrarian law reform heavily depends on synergy between regulatory updates, strengthening legal institutions, and community engagement. This article recommends consistent regulatory reforms, improved governance of agrarian resources, and the integration of social justice principles in decision-making processes. These findings provide a significant contribution to the development of an inclusive, equitable, and sustainable agrarian legal framework in Indonesia.